Efektivitas Penggunaan Metode Iqro Dalam Belajar Membaca Al-Qur’an Pada Anak Anak Desa Lantosan 1 - Apsah Apsah; Ahmad Mashudi; Khollis Martua; Muhammad Rasid; Ramadani Dalimunthe; Ropikoh Nur Lubis; Saydah Husni Hasibuan; Susi Hariyani; Windah Nur Siregar (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Iqro is a book used and intended for children to be able to read the Qur'an proficiently. Iqra is a very basic method for anyone who wants to read the Qur'an fluently. The hope of studying the book is to understand in accordance with the science of tajweed, both in terms of makharijul letters, idzhar, ikhfa and other reading laws. Teaching Qur'an reading to children aged six to fourteen is not easy. It can also be used to teach teenagers who can't recite. This study aims to determine the application of the IQRA method used during the teaching process in Lantosan 1 Village, Portibi District. As a result of this devotion, children can love the Qur'an more than before and are able to practice the teachings of Islam